Grayscale regulation and control display structure based on phase change material

By introducing a dielectric layer and a thermal isolation layer into the phase change display structure, changing the crystallization temperature of the phase change material, the difficulty of the same phase change material in gray scale adjustment is solved, and multi-gradient graying for phase change display devices is achieved Degree adjustment, suitable for most phase change materials, with a simple structure and easy to integrate.

CN119310757AActive Publication Date: 2025-01-14HUAZHONG UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411658208.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the existing phase change display technology, it is difficult to use the same phase change material for grayscale adjustment, especially because the crystallization temperature of the same phase change material is the same, which makes it difficult to adjust grayscale in multi-layer designs.

Method used

Design a grayscale regulation display structure for a base phase change material. By introducing a dielectric layer and a thermal isolation layer into the phase change material layer, different dielectric materials are used to change the crystallization temperature of the phase change material, and realize multi-gradient through electrical heating drive. Grayscale adjustment. Specific measures include using the same phase change material to make the thickness of at least one layer less than 10 nm, or using different phase change materials to achieve a phase change temperature difference of greater than 30 degrees Celsius, combining a transparent thermal insulation layer and a transparent conductive metal layer to accurately regulate the phase. The crystallization state of the variable material.

Benefits of technology

Accurate grayscale regulation of phase change materials is realized, suitable for most phase change materials, with a simple structure, not easily affected by the environment, and is easy to integrate. It can be designed by changing the crystallization temperature of the same phase change materials, and overcomes the existing technology. The problem of unstable grayscale adjustment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119310757A_ABST
    Figure CN119310757A_ABST
Patent Text Reader

Abstract

The invention provides a gray scale regulation and control display structure based on a phase-change material, which comprises at least two phase-change material layers, and the crystallization temperature gradient of the phase-change material layers is at least more than 50 DEG C; the dielectric layers are arranged on the upper side and the lower side of each phase-change material layer, and the dielectric layers are used for changing the crystallization temperature of the phase-change material layers; the thermal isolation layer is located between the phase change material layers; and the electrode layer is positioned on one side or two sides of the dielectric layer and is used for performing electric heating driving on the phase change material layer. The phase change display device can be subjected to accurate gray scale adjustment, is suitable for most phase change materials, and is simple in structure, not prone to being affected by the environment and easy to integrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phase change display, and in particular to a grayscale control display structure based on phase change material. Background Art

[0002] Phase change display technology is unique among many display technologies, and its advantages are particularly obvious in comparison. Compared with traditional liquid crystal display (LCD) technology, phase change display does not require backlight, so it is superior in black display and energy consumption. LCD relies on polarized light and the rotation of liquid crystal molecules to control the display content, which limits its response speed and contrast performance, while phase change display directly adjusts the transmittance of light through the phase change of the material, providing faster response time and higher contrast.

[0003] Compared with Organic Light Emitting Diode (OLED) technology, phase change display also exhibits non-volatile characteristics. OLED displays black by turning off pixels, while phase change display absorbs light through the amorphous state of the material, thereby achieving true black display and avoiding the common burn-in problem in OLED. In addition, the manufacturing cost and material life of OLED are also challenges it faces. Phase change display technology, due to its material properties and simple manufacturing process, shows potential advantages in cost-effectiveness and durability.

[0004] Electrophoretic display (EPD) technology, such as electronic ink, is favored for its low power consumption and paper-like reading experience, but its refresh rate is slow and not suitable for dynamic image display. Phase change display technology provides a faster refresh rate and a wider color gamut, making it more advantageous in displaying dynamic content.

[0005] In general, phase change display technology combines the advantages of fast response, high contrast, non-volatility, low energy consumption and flexible form, which enables it to show unique application potential and market prospects in the competition with traditional display technologies such as LCD, OLED and EPD.

[0006] In the phase change display technology based on FP (Fabry-Perot) cavity, the thinner the phase change layer, the greater the optical contrast and the better the display performance. However, the thinner the phase change film, the more difficult it is to change phase, especially for the grayscale adjustment of the same phase change material, because the crystallization temperature of the same phase change material is the same, which makes grayscale adjustment more difficult in a multi-layer design. Summary of the invention

[0007] The present invention provides a grayscale control display structure based on phase change materials, which is used to solve the defect that grayscale control using phase change materials in the prior art is difficult, and realizes multi-gradient grayscale control using phase change materials.

[0008] The present invention provides a grayscale control display structure based on a phase change material, comprising:

[0009] A phase change material layer, wherein the phase change material layer comprises at least two layers, and the crystallization temperature gradient of the phase change material layer is at least above 30 degrees Celsius;

[0010] A dielectric layer, wherein each phase change material layer has a dielectric layer on both sides thereof, and the dielectric layer is used to change the crystallization temperature of the phase change material layer;

[0011] A thermal isolation layer, located between the phase change material layers;

[0012] The electrode layer is located on one side or both sides of the dielectric layer and is used to electrically heat and drive the phase change material layer.

[0013] According to a phase-change material-based grayscale control display structure provided by the present invention, the phase-change material layers use the same phase-change material, and the thickness of at least one layer of the same phase-change material layers is less than 10 nm.

[0014] According to a phase-change material-based grayscale control display structure provided by the present invention, the phase-change material layers use different types of phase-change materials, and the phase-change temperature difference between different phase-change material layers is greater than 30 degrees Celsius.

[0015] According to a grayscale control display structure based on a phase change material provided by the present invention, the thermal isolation layer is provided between two adjacent phase change material layers;

[0016] In the electric heating drive, the temperature on both sides of the thermal isolation layer is greater than the phase change temperature of the phase change material layer on one side of the thermal isolation layer;

[0017] The thermal insulation layer has a transparent property.

[0018] According to a grayscale control display structure based on a phase-change material provided by the present invention, the phase-change material used in the phase-change material layer is a chalcogenide compound and its alloy, and the phase-change material includes one or more of GST, GSST, IST, GeTe, SbTe, BiTe, InSb, InSe, GeSb, GaSb, GaSb, GeSbTe, AgInSbTe, InSbTe, AgSbTe, Ag2In4Sb76Te17 (AIST), SbSe and SbS;

[0019] The phase change material has a chemical formula having variable atomic percentages and includes at least one dopant.

[0020] According to a grayscale control display structure based on a phase change material provided by the present invention, the crystallization temperature of the phase change material layer is increased or decreased through the induction or other effects of the dielectric layer.

[0021] According to a grayscale control display structure based on a phase change material provided by the present invention, the phase change material layer includes a first phase change material layer and a second phase change material layer, the dielectric layer includes a first dielectric layer, a second dielectric layer and a third dielectric layer, and the electrode layer includes a first metal layer, a second metal layer and a third metal layer;

[0022] The first metal layer, the first dielectric layer, the first phase-change material layer, the second dielectric layer, the second metal layer, the third dielectric layer, the second phase-change material layer and the third metal layer are arranged in sequence from bottom to top.

[0023] According to a phase-change material-based grayscale control display structure provided by the present invention, the first metal layer is a reflective layer, and the first metal layer and / or the second metal layer are used to drive the first phase-change material layer to undergo phase change;

[0024] The first dielectric layer and the second dielectric layer are used to change the crystallization temperature of the first phase change material layer;

[0025] The third metal layer is used as a dielectric layer and the third dielectric layer is used to change the crystallization temperature of the second phase change material layer, and the third metal layer is used to drive the second phase change material layer to undergo phase change;

[0026] The third dielectric layer also serves as the thermal isolation layer.

[0027] According to a grayscale control display structure based on a phase change material provided by the present invention, the first metal layer is a transparent metal with a light absorption rate less than a preset threshold among Ag, W, Al, Pt and Zn;

[0028] The second metal layer and the third metal layer are transparent conductive metals selected from ITO and INO.

[0029] According to a grayscale control display structure based on a phase change material provided by the present invention, the first dielectric layer or the second dielectric layer is a dielectric material selected from TiO2, TiN, SiO2 and Al2O3, and the thickness of the first dielectric layer and the second dielectric layer are 5nm to 500nm respectively, and the target display color of the grayscale control display structure corresponds to an integer multiple of one quarter of the wavelength ±10nm;

[0030] The third dielectric layer is a dielectric material selected from Al2O3 and SiO2.

[0031] The grayscale control display structure based on phase change material provided by the present invention is designed by using phase change material and dielectric induction material to design the display structure. When the dielectric material is combined with the phase change material, the crystallization characteristics of the phase change material are affected. The grayscale of the phase change material can be accurately controlled, and the grayscale of the phase change display device can be adjusted. It is suitable for most phase change materials, has a simple structure, is not easily affected by the environment, is easy to integrate, and can be designed by changing the crystallization temperature of the same phase change material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a schematic diagram showing the relationship between the thickness of the phase change display material GST and the influence of TiN and Al2O3 interface materials on its crystallization temperature in the grayscale control display structure based on the phase change material provided by the present invention;

[0034] Figure 2 It is a schematic diagram of a phase change temperature test structure of two layers of dielectric materials and phase change materials in a grayscale control display structure based on phase change materials provided by the present invention;

[0035] Figure 3 It is a schematic diagram of the distribution of crystalline and amorphous curves of the dielectric material (ZnS) 0.85 (SiO) 0.15 sandwiching the phase change material GST in the grayscale control display structure based on the phase change material provided by the present invention;

[0036] Figure 4 It is a schematic diagram of the grayscale control display structure distribution based on phase change material provided by the present invention;

[0037] Figure 5 It is a schematic diagram of the optical structure reflectivity of the grayscale control display structure based on the phase change material provided by the present invention.

[0038] Reference numerals:

[0039] 201, a first dielectric layer of a phase change temperature test structure, 202, a phase change material layer of a phase change temperature test structure, 203, a second dielectric layer of a phase change temperature test structure, 401, a first metal layer of a display structure, 402, a first dielectric layer of a display structure, 403, a first phase change material layer of a display structure, 404, a second dielectric layer of a display structure, 405, a second metal layer of a display structure, 406, a third dielectric layer of a display structure, 407, a second phase change material layer of a display structure, 408, a third metal layer of a display structure. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In the existing display technology, the phase change display structure composed of a broadband absorption structure and a narrowband absorption structure composed of a dielectric layer and a metal material mainly adjusts the grayscale by adjusting the crystallization degree of the phase change material. However, it is difficult to adjust the crystallization ratio, and the grayscale adjustment is unstable. Alternatively, different phase change materials with very different phase change temperatures are used to adjust the grayscale, but the selection range of display materials is limited to different material combinations and becomes very small. Alternatively, the grayscale is adjusted using the same phase change material through the driving voltage of different layers. However, since the crystallization temperature of the same phase change material is the same, it is difficult to control the phase change of only one layer without affecting the phase change of other layers, which will produce great thermal crosstalk, which will greatly hinder its further application. Therefore, it is of great practical significance to design a display technology for precise grayscale control of the same phase change material.

[0042] Combine the following Figures 1 to 5 The present invention describes a grayscale control display structure based on phase change material, comprising:

[0043] A phase change material layer, wherein the phase change material layer comprises at least two layers, and the crystallization temperature gradient of the phase change material layer is at least above 30 degrees Celsius;

[0044] A dielectric layer, wherein each phase change material layer has a dielectric layer on both sides thereof, and the dielectric layer is used to change the crystallization temperature of the phase change material layer;

[0045] A thermal isolation layer, located between the phase change material layers;

[0046] The electrode layer is located on one side or both sides of the dielectric layer and is used to electrically heat and drive the phase change material layer.

[0047] This embodiment uses different dielectric layers to affect the crystallization temperature of the phase change material layer. By selecting dielectric materials that can affect the crystallization temperature of the phase change material to be high or low, the phase change material is designed for display to achieve multi-gradient grayscale adjustment.

[0048] The display design is based on the characteristics that the thinner the phase change material, the higher the temperature required for the phase change, and different dielectric layers will affect the conversion temperature of its phase change. Since the thinner the phase change material, the better the optical properties, the better the display effect before and after the phase change, and the crystallization temperature is more affected by the dielectric material. Based on this, by selecting materials that can reduce its crystallization temperature, the corresponding design is carried out according to the degree of reduction.

[0049] Figure 2 The phase change temperature test structure includes, from bottom to top, a first dielectric layer 201, a phase change material layer 202, and a second dielectric layer 203. In the phase change temperature test structure, two layers of dielectric materials sandwich the phase change material, and the phase change temperature thereof is measured along with the change of the thickness of the phase change material. Figure 1 and Figure 3 The curve graph in Figure 2 Based on the test.

[0050] Figure 1 The red curve in the middle is the curve of TiN sandwiching the phase change material as the thickness of the phase change material changes, and the black line is the curve of Al2O3 sandwiching the phase change material as the thickness of the phase change material changes. It can be seen that as the thickness of the phase change material decreases, the crystallization temperature of the phase change material will gradually increase, and the phase change material will be greatly affected by the dielectric material.

[0051] Based on this, we can use the property that the thinner the phase change material is, the greater the influence of the dielectric material on its crystallization temperature. Moreover, the thinner the phase change material is, the better its performance before and after the phase change in the display structure is, and the phase change material is easy to completely crystallize. Adding a heat insulation layer with good heat insulation performance between different phase change material layers can further avoid crosstalk during the crystallization of the phase change layer during the phase change display process.

[0052] In general, this embodiment adopts a new display structure design idea and successfully develops a display technology that can accurately control its grayscale to meet the demand for grayscale control based on the reflective display market. This technical strategy overcomes the inherent limitations of the existing structure, has a significant technological advancement significance, and opens up new possibilities for the further development of phase change display technology.

[0053] This embodiment designs a display structure by using phase change material and dielectric induction material. When the dielectric material is combined with the phase change material, it affects the crystallization characteristics of the phase change material. The grayscale of the phase change material can be accurately controlled, and the grayscale of the phase change display device can be adjusted. It is suitable for most phase change materials, has a simple structure, is not easily affected by the environment, is easy to integrate, and can be designed by changing the crystallization temperature of the same phase change material.

[0054] On the basis of the above-mentioned embodiment, the phase change material layers in this embodiment use the same phase change material, and at least one layer of the same phase change material layer has a thickness of less than 10 nm.

[0055] If the multiple phase change material layers in the display structure use the same phase change material, at least one layer has a thickness less than 10 nm, preferably less than or equal to 6 nm.

[0056] As the thickness of the phase change material decreases, the phase change temperature increases when it is less than 10nm. This is because the thinner the film is, the more difficult it is for the phase change material to nucleate in the vertical direction, and the role of the coating layer wrapped around the phase change material becomes more and more important.

[0057] Taking GST as an example, it is crucial to ensure that the volume of the phase change material GST is sufficient to maintain vacancies and stability in the cubic phase through resonant bonding. A film as thin as 2 nanometers can crystallize, which is close to the minimum thickness at which resonant bonding can stabilize the cubic phase. The compressive stress increases the energy required for the Ge atoms to transform from tetrahedral to octahedral coordination, thereby increasing the crystallization temperature. Materials such as TiN and Al2O3 tend to cause a sharp increase in crystallization temperature, while (ZnS)0.85(SiO)0.15, which applies lower stress, has little effect on the crystallization temperature, and this point can be used for corresponding design.

[0058] On the basis of the above embodiment, the phase change material layer in this embodiment uses different types of phase change materials, and the phase change temperature difference of different phase change material layers is greater than 30 degrees Celsius.

[0059] On the basis of the above embodiment, in this embodiment, the thermal isolation layer is provided between two adjacent phase change material layers;

[0060] In the electric heating drive, the temperature on both sides of the thermal isolation layer is greater than the phase change temperature of the phase change material layer on one side of the thermal isolation layer;

[0061] The thermal insulation layer has a transparent property.

[0062] A thermal isolation layer is added between different phase change material layers, and the thermal insulation material used is transparent and has a low light absorption rate.

[0063] On the basis of the above embodiments, the phase change material used in the phase change material layer in this embodiment is a chalcogenide compound and its alloy, and the phase change material includes one or more of GST, GSST, IST, GeTe, SbTe, BiTe, InSb, InSe, GeSb, GaSb, GaSb, GeSbTe, AgInSbTe, InSbTe, AgSbTe, Ag2In4Sb76Te17 (AIST), SbSe and SbS;

[0064] The chemical formula of the phase change material has a variable atomic percentage and contains at least one dopant, such as C and N.

[0065] On the basis of the above embodiments, in this embodiment, the crystallization temperature of the phase change material layer is increased or decreased through the induction or other effects of the dielectric layer.

[0066] The influence of the dielectric material on the thin layer of phase change material can be divided into two categories: reducing the phase change temperature or increasing the phase change temperature. By combining dielectric materials, the temperature gradient of the phase change material is large, and this design can accurately control its grayscale.

[0067] Based on the above embodiments, Figure 4 As shown, in this embodiment, the phase change material layer includes a first phase change material layer 403 and a second phase change material layer 407, the dielectric layer includes a first dielectric layer 402, a second dielectric layer 404 and a third dielectric layer 406, and the electrode layer includes a first metal layer 401, a second metal layer 405 and a third metal layer 408;

[0068] The first metal layer 401 , the first dielectric layer 402 , the first phase change material layer 403 , the second dielectric layer 404 , the second metal layer 405 , the third dielectric layer 406 , the second phase change material layer 407 and the third metal layer 408 are arranged in sequence from bottom to top.

[0069] On the basis of the above embodiment, in this embodiment, the first metal layer 401 is a reflective layer, and the first metal layer 401 and / or the second metal layer 405 are used to drive the first phase change material layer 403 to undergo phase change;

[0070] The first dielectric layer 402 and the second dielectric layer 404 are used to change the crystallization temperature of the first phase change material layer 403;

[0071] The third metal layer 408 is used as a dielectric layer and together with the third dielectric layer 406 to change the crystallization temperature of the second phase-change material layer 407 . The third metal layer 408 is used to drive the second phase-change material layer 407 to undergo phase change.

[0072] The third dielectric layer 406 also serves as the thermal isolation layer.

[0073] The first metal layer 401 may be made of metal Ag, which mainly serves as a reflective layer and provides heat to drive the first phase change material layer 403 to undergo phase change.

[0074] The first dielectric layer 402 may be made of dielectric TiN. The first phase-change material layer 403 may be made of phase-change material GST. The second dielectric layer 404 may be made of dielectric TiN, and mainly changes the crystallization temperature of the first phase-change material layer 403 together with the first dielectric layer 402 .

[0075] The second metal layer 405 may be ITO, providing a dielectric layer for the FP cavity. The third dielectric layer 406 may be Al2O3, mainly used together with the third metal layer 408 to change the crystallization temperature of the second phase change material layer 407 thin film.

[0076] The second phase change material layer 407 may be made of phase change material GST. The third metal layer 408 may be ITO, which mainly provides heat drive and also serves as a dielectric layer of the FP cavity.

[0077] The design mainly utilizes the TiN of the first dielectric layer 402 and the second dielectric layer 404 to change the phase change temperature of GST, and also uses Al2O3 to change the temperature of the phase change material layer. This allows the same phase change material to have different temperature gradients, which can control the phase change of different layers of phase change materials, thereby regulating the grayscale of the display device. At the same time, Al2O3 has a heat-insulating effect, which prevents thermal crosstalk between the phase change material layers when they change phase.

[0078] The phase change materials of the first phase change material layer 403 and the second phase change material layer 407 can be converted between a crystalline state and an amorphous state under electrical stimulation or laser stimulation, thereby causing the transmittance and reflectivity of the phase change layer to change.

[0079] Metal ITO is deposited on the top second phase change material layer 407. The second phase change material layer 407 can control the crystallization state of the phase change material by applying voltage on the third metal layer 408 ITO. The first phase change material layer 403 can control the crystallization state of the phase change material by applying voltage on the first metal layer 401Ag or the second metal layer 405ITO.

[0080] Specifically, a pulse voltage or laser pulse of medium intensity is applied to the first phase change material layer 403 or the second phase change material layer 407. Under the action of the current or laser pulse, the temperature of the phase change material rises to a temperature range above the crystallization temperature and below the melting temperature and is maintained for a certain period of time. At this time, the crystal lattice is orderly arranged to form a crystalline state, realizing the transition from amorphous to crystalline.

[0081] A short and strong voltage or laser pulse is applied to the first phase change material layer 403 or the second phase change material layer 407 to raise the temperature of the phase change material to above the melting temperature, thereby destroying the long-range order of the crystalline state. The pulse falling edge is very short, causing the phase change material to be quickly cooled to below the crystallization temperature, so that the phase change material is fixed in the amorphous state, thereby realizing the transition from the crystalline state to the amorphous state. The grayscale of the phase change material is regulated by the changes in the transmittance and reflectivity of the phase change material of the first phase change material layer 403 or the second phase change material layer 407 when the phase change material is transformed between the amorphous state and the crystalline state.

[0082] On the basis of the above embodiment, in this embodiment, the first metal layer 401 is a transparent metal such as Ag, W, Al, Pt and Zn, whose light absorption rate is less than a preset threshold, and its thickness is greater than 50nm, and light cannot pass through;

[0083] The second metal layer 405 and the third metal layer 408 are transparent conductive metals such as ITO and INO.

[0084] On the basis of the above embodiment, in this embodiment, the first dielectric layer 402 or the second dielectric layer 403 has an influence on the temperature of the thin phase change layer. When designing, the phase change materials between different layers must have a sufficiently large temperature gradient, which can be dielectric materials such as TiO2, TiN and Al2O3. The thickness of the first dielectric layer and the second dielectric layer are 5nm to 500nm respectively, and the color corresponding to the color to be displayed by the grayscale control display structure is obtained by an integer multiple of one quarter of the wavelength ±10nm;

[0085] The third dielectric layer 406 mainly plays a role of heat insulation and can be made of dielectric materials such as Al2O3 and SiO2.

[0086] Figure 5 yes Figure 4 The spectral distribution of a combination of the structures shown. CC indicates that both the first phase change material layer and the second phase change material layer are crystalline, AC indicates that the first phase change material layer is amorphous and the second phase change material layer is crystalline, AA indicates that both the first phase change material layer and the second phase change material layer are amorphous, and CA indicates that both the first phase change material layer is crystalline and the second phase change material layer are amorphous. Preferably, the first metal layer 401 is Ag with a thickness of 100nm, the first dielectric layer 402 has a thickness of 20nm, the first phase change material layer 403 has a thickness of 4nm, the second dielectric layer 404 has a thickness of 20nm, the second metal layer 405 has a thickness of 210nm, the third dielectric layer 406 has a thickness of 10nm, the second phase change material layer 407 has a thickness of 4nm, and the third metal layer 408 has a thickness of 10nm. From Figure 5 It can be seen that when the phase change layer is in different states, its display is also different.

[0087] pass Figure 1 It can be seen that the dielectric TiN on both sides sandwich the phase change material GST. When it is 4nm, its phase change temperature is about 225℃. The dielectric Al2O3 on both sides sandwich the phase change material GST. When it is 4nm, its phase change temperature is about 350℃. The temperature difference is about 100℃. This gradient can be used to design phase change display.

[0088] Similarly, from Figure 3It can be seen that the GST sandwiched by (ZnS)0.85(SiO)0.15 affects its temperature, lowering the temperature of its phase change. This characteristic can be used to design the gradient of phase change display, and then adjust the grayscale of the display device.

[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A grayscale control display structure based on phase change material, characterized in that: include: A phase change material layer, wherein the phase change material layer comprises at least two layers, and the crystallization temperature gradient of the phase change material layer is at least above 30 degrees Celsius; A dielectric layer, wherein each phase change material layer has a dielectric layer on both sides thereof, and the dielectric layer is used to change the crystallization temperature of the phase change material layer; A thermal isolation layer, located between the phase change material layers; The electrode layer is located on one side or both sides of the dielectric layer and is used to electrically heat and drive the phase change material layer.

2. The grayscale control display structure based on phase change material according to claim 1, characterized in that: The phase change material layers are made of the same phase change material, and at least one layer of the same phase change material layers has a thickness of less than 10 nm.

3. The grayscale control display structure based on phase change material according to claim 1, characterized in that: The phase change material layers use different types of phase change materials, and the phase change temperature difference between different phase change material layers is greater than 30 degrees Celsius.

4. The grayscale control display structure based on phase change material according to claim 1, characterized in that: The thermal isolation layer is provided between two adjacent phase change material layers; In the electric heating drive, the temperature on both sides of the thermal isolation layer is greater than the phase change temperature of the phase change material layer on one side of the thermal isolation layer; The thermal insulation layer has a transparent property.

5. The grayscale control display structure based on phase change material according to claim 1, characterized in that: The phase change material used in the phase change material layer is a chalcogenide compound and its alloy, and the phase change material includes one or more of GST, GSST, IST, GeTe, SbTe, BiTe, InSb, InSe, GeSb, GaSb, GaSb, GeSbTe, AgInSbTe, InSbTe, AgSbTe, Ag2In4Sb76Te17 (AIST), SbSe and SbS; The phase change material has a chemical formula having variable atomic percentages and includes at least one dopant.

6. The grayscale control display structure based on phase change material according to claim 1, characterized in that: The crystallization temperature of the phase change material layer is increased or decreased through the induction or other effects of the dielectric layer.

7. The grayscale control display structure based on phase change material according to claim 1, characterized in that: The phase change material layer includes a first phase change material layer and a second phase change material layer, the dielectric layer includes a first dielectric layer, a second dielectric layer and a third dielectric layer, and the electrode layer includes a first metal layer, a second metal layer and a third metal layer; The first metal layer, the first dielectric layer, the first phase-change material layer, the second dielectric layer, the second metal layer, the third dielectric layer, the second phase-change material layer and the third metal layer are arranged in sequence from bottom to top.

8. The grayscale control display structure based on phase change material according to claim 7, characterized in that: The first metal layer is a reflective layer, and the first metal layer and / or the second metal layer are used to drive the first phase change material layer to undergo phase change; The first dielectric layer and the second dielectric layer are used to change the crystallization temperature of the first phase change material layer; The third metal layer is used as a dielectric layer and the third dielectric layer is used to change the crystallization temperature of the second phase change material layer, and the third metal layer is used to drive the second phase change material layer to undergo phase change; The third dielectric layer also serves as the thermal isolation layer.

9. The grayscale control display structure based on phase change material according to claim 7, characterized in that: The first metal layer is a transparent metal among Ag, W, Al, Pt and Zn, and its light absorption rate is less than a preset threshold; The second metal layer and the third metal layer are transparent conductive metals selected from ITO and INO.

10. The grayscale control display structure based on phase change material according to claim 7, characterized in that: The first dielectric layer or the second dielectric layer is a dielectric material selected from TiO2, SiO2, TiN and Al2O3, and the thickness of the first dielectric layer and the second dielectric layer are respectively 5nm to 500nm, obtained by an integer multiple of one quarter of the wavelength corresponding to the target display color of the grayscale control display structure ±10nm; The third dielectric layer is a dielectric material selected from Al2O3, SiO2, TiN and TiO2.

Citation Information

Patent Citations

  • Multi-valued phase change memory unit, phase change memory, electronic equipment and preparation method

    CN112820823A

  • Pixel structure and display driving method thereof

    CN116449629A

  • Building conditioning technique using phase change materials in the roof structure

    US20050178524A1

  • Phase change memory structure having low-k dielectric heat-insulating material and fabrication method thereof

    US20130175493A1